2021
DOI: 10.3390/rs13040804
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Transpiration with Sun-Induced Chlorophyll Fluorescence Observations via Carbon-Water Coupling Methods

Abstract: Successfully applied in the carbon research area, sun-induced chlorophyll fluorescence (SIF) has raised the interest of researchers from the water research domain. However, current works focused on the empirical relationship between SIF and plant transpiration (T), while the mechanistic linkage between them has not been fully explored. Two mechanism methods were developed to estimate T via SIF, namely the water-use efficiency (WUE) method and conductance method based on the carbon–water coupling framework. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…A previous study has developed an algorithm of GPP estimation using SIF products, which have global coverage and can be used in all weathers [81]. Studies have also shown the empirical and mechanistic relationship between T and SIF to improve the T estimation [82][83][84]. Due to weak signal strength of SIF and a weak relationship between T and SIF, T produced by SIF needs further evaluation and research considerations [85].…”
Section: Advances In Indirect Wue Estimation By Remote Sensingmentioning
confidence: 99%
“…A previous study has developed an algorithm of GPP estimation using SIF products, which have global coverage and can be used in all weathers [81]. Studies have also shown the empirical and mechanistic relationship between T and SIF to improve the T estimation [82][83][84]. Due to weak signal strength of SIF and a weak relationship between T and SIF, T produced by SIF needs further evaluation and research considerations [85].…”
Section: Advances In Indirect Wue Estimation By Remote Sensingmentioning
confidence: 99%